[Boats At Stykkishólmur Harbor] - Streng, Evelyn Fiedler (1975)
Photograph of boats along a harbor in Stykkishólmur, Iceland. White boats with red trimmings sits along a stone dock where a red car and a group of people stand to the right. A tall, brown, stone cliff covered in green grass sits to the left, a yellow lighthouse sat at the top of it. A flat mountain is visible in the background to the right. Dark ocean water surrounds the structures, rippled and reflecting back the boats and lighthouse.